Studi Perbedaan Kualitas Produksi Minyak Goreng Kemasan A Dan B Serta Curah - Syafrinal Syafrinal; Pevi Riani; Selfa Dewati Samah (Universitas Muhammadiyah Sorong, 2023)
Differences in the quality of bulk and packaged cooking oil are caused by differences in the quality of raw materials and production processes. This study aims to compare the quality of packaged cooking oil A and B also bulk which have been produced before being marketed. This research is a quantitative approach that focuses on the analysis of Free Fatty Acid, Moisture & Impurities, Iodine Value, Peroxide Value, color, stability, cloud point and pelican oil on packaged cooking oil A and B also bulk. The results showed that the test parameter values ​​for packaged cooking oil A and B also bulk were 0.064 %, 0.065 % and 0.068 % for FFA. M & I content were 0.040 %, 0.045 % and 0.046 %. 60,887; 59,034; and 57,416 g I2/100 mg oil were the IV values. The PV values were 0.098; 0.102; and 1,58 Mek O2/Kg. 1.9/46 Red/Yellow, 2.1/51 Red/Yellow, and 2.3/51 Red/Yellow are the color values. For stability, timers for 10 minutes, 5 minutes, and 1 minute. Cloud point temperatures were 4.4°C, 7.4°C, and 9.8°C and negative results on the pelican oil test. The obtained packaged cooking oil A is of higher quality than packaged cooking oil B and bulk.